Beethoven as a young man - Weger, August, 1823-1892 (engraver):::Creator::::::::::::; Weger, Th. (engraver):::Contributor::::::::::::; Stainhauser, Gandolph Ernst, 1766-1805 (artist):::Contributor:::::::::::: (Augener; United Kingdom; London, 2020)
Portrait engraving of Ludwig van Beethoven as a young man, by Th. and August Weger, based on a drawing by Gandolph Ernst Stainhauser.